Perbandingan Pola Rasio Morfometrik dan Karakteristik Habitat Dua Spesies Ikan Cupang Alam (Betta spp.) Endemik Pulau Bangka - Ramadhanu, Destra; Prananda, Mustobi; Wulandari, Ufi Ayu; Hidayat, Rahmad; Syarif, Ahmad Fahrul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Bangka Island has extraordinary biodiversity. Bangka Island has various types of freshwater fish, including local and endemic fish. The natural betta fish Betta burdigala and Betta chloropharynx are two species of fish endemic to Bangka Island which are considered endangered. The aim of this study was to analyze the differences in morphology and habitat characteristics between these two species. This research uses a quantitative descriptive approach. The fish samples used were 10 Betta burdigala and Betta chloropharynx fish taken from Bikang Village, South Bangka Regency and Jade Bahrin Village, Bangka Regency from August to September 2023. The data obtained were analyzed descriptively and presented as graphs or tables. There are eight main characteristics based on morphometric ratios, namely Total Length (TL), Body Length (BL), Tail Length (TL), Head Length (HL), Head Height (HH), Body Width-I (BW-I), Body Width-II (BW-II), and Body Width-III (BW-III). Based on morphometric ratios, there are differences in all morphometric characters. Betta burdigala and Betta chloropharynx live in peat swamp waters, the pH of Betta burdigala water is lower than the pH of Betta chloropharynx water, the color of Betta burdigala water is more black brown, while the color of Betta chloropharynx water is clearer.